Voacafrines A-N, aspidosperma-type monoterpenoid indole alkaloids from Voacanga africana with AChE inhibitory activity. (January 2021) - Zhao, Qian; Zhu, Wen-Tao; Ding, Xiao; Huo, Zong-Qing; Donkor, Paul O.; Adelakun, Tiwalade A.; Hao, Xiao-Jiang; Zhang, Yu
Abstract: Fourteen undescribed monoterpenoid indole alkaloids, voacafrines A-N, along with 7 known monoterpenoid indole alkaloids were isolated from the seeds of Voacanga africana Stapf. Among them, voacafrines A-G were aspidosperma-aspidosperma type bisindole alkaloids, while voacafrines H–N were aspidosperma-type monomers. Their structures and absolute configurations were elucidated by a combination of NMR, MS, and ECD analyses. Voacafrines A-C were characterized by an acetonyl moiety at C-5′, while voacafrine H possessed a methoxymethyl moiety at C-14 within aspidosperma-type alkaloids. The acetylcholinesterase (AChE) inhibitory activity and cytotoxicity of voacafrines A-N were evaluated. Voacafrines A-C and E-G were bisindole alkaloids that exhibited AChE inhibitory activity with IC50 values of 4.97–33.28  μ M, while voacafrines I and J were monomers that showed cytotoxicity against several human cancer cell lines with IC50 values of 4.45–7.49  μ M. Graphical abstract: Fourteen undescribed monoterpenoid indole alkaloids, voacafrines A-N, were isolated from the seeds of Voacanga africana . Bisindole alkaloids voacafrines A-C, and E-G exhibited moderate acetylcholinesterase (AChE) inhibitory activity with IC50 values of 4.97-33.28 μ M. Image 1 Highlights: Fourteen undescribed monoterpenoid indole alkaloids, voacafrines A-N, were isolated from the seeds of Voacanga africana. The structures of voacafrines A-N were elucidated by a combination of NMR, MS, and ECD analyses. Bisindole alkaloids voacafrines A-C are characterized by an acetonyl moiety at C-5′. Voacafrines A-C, E-G exhibited acetylcholinesterase (AChE) inhibitory activity with IC50 values of 4.97–33.28  μ M. Voacafrines I and J showed cytotoxicity against several human cancer cell lines with IC50 values 4.45–7.49  μ M.